Ações afirmativas e a neutralidade liberal - Franklin Vinícius Marques Dutra (2023)
From the discussion on affirmative action policies, this work seeks to gain a better understanding of the meaning of some fundamental concepts in John Rawls's more mature works, especially his publication of Political Liberalism. In this book, Rawls delves deeply into the domain of the political to understand how a society divided by reasonable pluralism can be stable for the right reasons. In essence, his argument is that despite insurmountable disagreement among individuals who hold reasonable comprehensive doctrines, it is possible to achieve an overlapping consensus through a political conception of justice. This consensus is reached by the use of public reason, which serves as both a procedural filter for argumentation and a substantive guide for addressing fundamental values. According to Rawls, only conceptions that meet the criterion of reciprocity are eligible as political conceptions of justice, thus ensuring the liberal principle of political legitimacy. In this sense, the aim is to understand how such a proposal can politically legitimize affirmative actions based on a political conception of justice and not as a promotion of a specific conception of the good, respecting the liberal neutrality from a justificatory standpoint. Furthermore, to support this claim, it is necessary to better understand the meaning of liberal neutrality and, especially, address Joseph Raz's proposal of perfectionist liberalism, which argues that autonomy is a value that the state should pursue. Through this analysis, the goal is not only to reinforce the political legitimacy of affirmative action according to the political conception of justice but also to outline reasons for the superiority of the political liberalism proposal over that of perfectionist liberalism.